Причини та наслідки утворення забарвлених стічних вод текстильних виробництв - Крючкова, В. В. (ФОП Яроченко Я. В., 2024)
Textile products are characterised not only by the quality of their fibre, but also by the quality of their colour. The processes of dyeing textiles are quite complex, resource-intensive and have a high percentage of waste. Waste from the dyeing process mainly includes wastewater with a high content of dye, acids and other chemically active substances. Dyed wastewater discharged into water bodies is dangerous because it affects the light transmission of water and the assimilation of algae, as well as changes the chemical composition.
Keywords: стічні води; текстильні виробництва; текстильна продукція; барвники; навколишнє середоище; канцерогенні речовини